Financing of the Construction Strategy of Leningrad During the Siege (1941-1944) - Zotova Anastasiya Valeryevna (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
In the article on the basis of archival documents the strategy of public authorities aimed at organizing in Leningrad construction, rehabilitation and repair works carried out in 1941-1944, is investigated, the activity of Leningrad lending institutions (Leningrad communal Bank and Agricultural Bank), which provided loans to enterprises, institutions and residents of Leningrad on various types of construction, is analyzed. Leningrad banks performed two main functions: control over the licit distribution of funds in construction organizations that were responsible for operational and residential buildings in Leningrad and providing citizens with affordable loans to buy and build houses. The author presents statistical information on the number of building and installation companies on the eve of the Great Patriotic War and during the siege of Leningrad. In the article the dynamics of building frames in different periods of the war is traced, the sharp deterioration in the training associated with the fact that most of the builders went into the Red army is noted. The article also notes the role of banks in preventing unfair wage calculation, which was carried out by the construction organizations. On the basis of study of experience of Leningrad banks activity in the extreme conditions of the siege, the author makes a conclusion about the effectiveness of the measures undertaken by the Central government and the local authorities on lending to government organizations and individuals. The author points to the important experience of enterprises, which become guarantors for their employees to banks. As a result, the employees received money at a lo interest rate. The author believes that this contributed to increased responsibility of workers for the results of their work that eventually affected the efficiency of enterprises. According to the author, it is necessary to use the historical experience of financing of enterprises, institutions and citizens especially in the current conditions of sanctions against the Russian Federation.